BIOM-01. GENOMIC ALTERATIONS IN ALK FUSION-POSITIVE NON-SMALL CELL LUNG CANCER (NSCLC) PATIENTS WITH BRAIN METASTASES. (14th November 2022) - Eichholz, Jordan; Miao, Emily; Lebow, Emily; Walch, Henry; Flynn, Jessica; Zhang, Zhigang; Hubbeling, Harper; Beal, Kathryn; Moss, Nelson; Yu, Kenny; Yang, Jonathan; Meng, Alicia; et al.
Abstract: PURPOSE: Brain metastases (BM) are common in patients with anaplastic lymphoma kinase fusion-positive NSCLC (ALK+ NSCLC). We characterized the genomics of patients with ALK+ NSCLC BM treated with alectinib with or without local therapy to identify correlations of co-mutations with CNS-specific outcomes. METHODS: We retrospectively reviewed ALK+ NSCLC patients with BMs who received alectinib for the definitive treatment of BM from 1/2012 and 5/2021. Genomic characteristics of 27 specimens from 27 patients were assessed with MSK-IMPACT, a 505-gene next-generation sequencing (NGS)-based tumor sequencing assay with >700x coverage. Intracranial progression-free survival (iPFS) and overall survival (OS) from BM diagnosis were analyzed using standard statistical methods. RESULTS: The median age at BM diagnosis was 57 years (range 25-83). Median iPFS was 1.94 years (95%CI: 1.58- not reached) and median OS was 6.08 years (95%CI: 1.7– not reached). All patients received alectinib for the treatment of brain metastases (78% as 1st-line TKI) and 22% received local therapy. The most frequently altered co- alterations were CDKN2A (48%), TP53 (22%), MAP2K4 (15%), SMARCA4 (11%), CREBBP (11%), and ATM (7%). CDKN2A alterations were more common in patients with intracranial progression (64% vs 31%). MAP2K4 alterations were enriched in metastatic samples (p = 0.028, q = 0.113). SMARCA4 co- alterations were associated with inferior OS (HR: 8.76, 95%CI = 1.74-44.2, p= 0.009) and trended toward association with iPFS but was insignificant (HR: 3.25, 95%CI = 0.83-12.4, p=0.089). We identified missense ALK alterations in CSF from a patient who acquired resistance to alectinib and had leptomeningeal progression (G1269A, I1171T, L1108P). CONCLUSION: This study is the first analysis of CNS specific outcomes with detailed genomic annotation for ALK+ NSCLC patients who received definitive alectinib for BM. Further investigation into the role of CNS-penetrant TKIs and the genomic alterations predictive of CNS failure are needed.